Fungsi Distribusi Statistik tN dalam Suatu Penyebaran Individu yang Beraturan dalam Bentuk Hexagon - M.A. Djauhari (Journal of Mathematical and Fundamental Sciences, 1981)
Sari. Statistik pengujian keacakan suatu penyebaran individu pada bidang datar selalu didasarkan pada hipotesis awal H0 bahwa penyebaran individu merupakan suatu realisasi dari suatu proses Poisson. Selanjutnya sebagai hipotesis alternatif biasa dipergunakan;(i). H11 : penyebaran individu merupakan suatu realisasi dari suatu proses Thomas.(ii). H12 : penyebaran individu adalah teratur dalam bentuk segitiga-segitiga sama sisi.(iii). H13 : penyebaran individu adalah teratur dalam bentuk bujursangkar-bujursangkar. Abstract. In order to determine the index of randomness a spatial pattern of objects the null hypothesis Ho that our spatial pattern is a realization of a Poisson's process is needed. The alternative usually used are:(i). H11: the spatial pattern is a realization of a Thomas' process.(ii). H12: the spatial pattern is regular in the form of equilateral triangles.(iii). H13: the spatial pattern is regular in the form of squares.We propose here the fourth alternative H14 that the spatial pattern is regular in the form of hexagons. Our interest here is to study, under H14, the distribution of tN, i.e. the best test of randomness under the first three alternatives (Djauhari, 1977).